When money was in fashion : Henry Goldman, Goldman Sachs, and the founding of Wall Street - Fisher, June Breton (New York : Palgrave MacMillan, 2010)
'This epic biography tells the story of the rise of Wall Street and the growth of Goldman Sachs from a small commercial paper company to the international banking business we know today. At its heart is the story of Henry Goldman, a man who spoke out passionately for his beliefs, understood the importance of the bottom line, and was known to chuckle, draw on his cigar, and remind his young proteges,'Just keep in mind ... Money is always in fashion.' Though you will rarely find a mention of him in the official history of Goldman Sachs, it was Henry who established many of the practices of modern investment banking. He devised the plan that made Sears, Roebuck Co. the first publicly owned retail operation in the world, helped convince Woodrow Wilson to pass the Federal Reserve Act of 1913, and became a power player in the world of Wall Street finance at a time when Jews were considered outsiders. The book traces Henry Goldman's hard-fought and often frustrating career with Goldman Sachs, a company founded by his father Marcus and fraught with professional rivalries. The tensions between the Goldman and Sachs families extended outside of the boardroom and into the larger world as the United States went to war. Henry's steadfast support for Germany during World War I would tarnish his reputation and drive him from the firm. But his involvement with finance would continue throughout his life, as would close friendships with luminaries like Albert Einstein, whom he would later join in outspoken denunciation of Hitler's atrocities against European Jews. Here, June Breton Fisher, Henry Goldman's granddaughter, tells his whole story for the first time-- a story that has shaped contemporary finance and continues to resonate with us today'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Goldman, Henry, -- 1857-1937.; Goldman, Sachs & Co. -- History; Investment banking -- United States -- History; Investment bankers -- United States -- Biography